Self‐Forming p–n Junction Diode Realized with WSe2 Surface and Edge Dual Contacts. Issue 46 (10th October 2022) - Le Thi, Hai Yen; Ngo, Tien Dat; Phan, Nhat Anh Nguyen; Yoo, Won Jong; Watanabe, Kenji; Taniguchi, Takashi; Aoki, Nobuyuki; Bird, Jonathan P.; Kim, Gil‐Ho
Abstract: Owing to their practical applications, two‐dimensional semiconductor p–n diodes have attracted enormous attention. Over the past decade, various methods, such as chemical doping, heterojunction structures, and metallization using metals with different work functions, have been reported for fabrication of such devices. In this study, a lateral p–n junction diode is formed in tungsten diselenide (WSe2 ) using a combination of edge and surface contacts. The appearance of amorphous tungsten oxide at etched WSe2, and the formation of a junction near the edge contact, are verified by high‐resolution transmission electron microscopy. The device demonstrates high on/off ratio for both the edge and surface contacts, with respective values of 10 7 and 10 8 . The diode can achieve extremely high mobility of up to 168 cm 2 V −1 s −1 and a rectification ratio of 10 3 . The ideality factor is 1.11 at a back gate voltage V G = 60 V at 300 K. The devices with encapsulation of hexagonal boron nitride exhibit good stability to atmospheric exposure, over a measured period of 2 months. In addition, the architecture of the contacts, which is based on a single‐channel device, should be advantageous for the implementation of more complicated applications such as inverters, photodetectors, and light‐emitting diodes. Abstract : In this study, a lateral p–n junction diode is formed in WSe2 using a combination of edge and surface contacts with extremely high performance. A rectification ratio of 10 3 and the ideality factor of 1.11 are achieved by the WSe2 single‐channel device. This should be advantageous for the implementation of more complicated applications such as inverters, photodetectors, and light‐emitting diodes.